(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Trusted Platform Module (TPM) on virtual machine system is a hardware-based root of trust. TPM saves the artefacts necessary to authenticate the computer’s platform integrity. The Trusted Computing Group was formed to ensure the Platform’s integrity is maintained through the Trusted Platform Module. We perform a thorough review of the literature on cryptographic primitives of trusted computing for infrastructure as a service in this paper. We discuss cloud computing as well as secure computing virtualization.